Dual Inhibition of Cdc7 and Cdk9 by PHA-767491 Suppresses Hepatocarcinoma Synergistically with 5-Fluorouracil - Li, Wei; Zhao, Xiao-Le; Shang, Shi-Qiang; Shen, Hong-Qiang; Chen, Xi (Current cancer drug targets, 2015)
Activation of checkpoint kinase 1 (Chk1) is essential in chemoresistance of hepatocarcinoma (HCC) to 5-fluorouracil (5-FU) and other antimetabolite family of drugs. In this study, we demonstrated that PHA-767491, a dual inhibitor of two cell cycle checkpoint kinases, cell division cycle kinase 7 (Cdc7) and cyclin-dependent kinase 9 (Cdk9), has synergistic antitumor effect with 5-FU to suppress human HCC cells both in vitro and in vivo. Compared with the sole use of each agent, PHA-767491 in combination with 5-FU exhibited much stronger cytotoxicity and induced significant apoptosis manifested by remarkably increased caspase 3 activation and poly(ADP-Ribose) polymerase fragmentation in HCC cells. PHA-767491 directly counteracted the 5-FU-induced phosphorylation of Chk1, a substrate of Cdc7; and decreased the expression of the anti-apoptotic protein myeloid leukemia cell 1, a downstream target of Cdk9. In tumor tissues sectioned from nude mice HCC xenografts, administration of PHA-767491 also decreased Chk1 phosphorylation and increased in situ cell apoptosis. Our study suggests that PHA- 767491 could enhance the efficacy of 5-FU by inhibiting Chk1 phosphorylation and down-regulating Mcl1 expression through inhibition of Cdc7 and Cdk9, thus combinational administration of PHA-767491 with 5-FU could be potentially beneficial to patients with advanced and resistant HCC.